Polypropylene and swine small intestinal submucosal meshes in repairs of defects on the abdominal wall of rats - Bürger, Camila Paes; De Araújo Machado, Marília Carneiro; Ferreira, Ana Raquel Araújo; Carneiro, Leandro Ziemer; Nunes, Newton [UNESP]; Da costa Neto, João Moreira (My University, 2016)
Among numerous diseases that affect humans and animals, the abdominal wall hernias are known since antiquity. There being no ideal surgical technique or study of a surgical procedure that stands out over the others, this study aimed to evaluate the behavior of polypropylene mesh (PP) and the submucosa membrane of small intestinal of swine (SIS) in defects repair on the abdominal wall of rat. The animals were divided into two groups with four experimental subgroups, corresponding to the observation time after surgery for PP and SIS (7, 15, 30 and 45 days). In the pressure test, the PP mesh was more resistant after 30 days of observation, since the SIS screen presented rupture in the suture region. Both groups showed inflammatory reaction, but in the SIS group the reaction was smaller and faster resolution. Collagen was seen in both groups with a predominance of collagen type I, in SIS Group the collagen was found in greater quantities since the beginning of the experiment and tissue organization was higher in SIS mesh. The two meshes are biocompatible; there is no superiority of any of the materials and were suggested the union of the two meshes for new studies.
Telas de polipropileno e de submucosa de intestino de suíno na reparação de falhas na parede abdominal de ratos
Keywords: Abdomen; Biomaterials; Incisional hernia; Surgery; Wound healing